Pengaruh Kreativitas Iklan, Unsur Humor, Daya Tarik Iklan Dan Kualitas Pesan Iklan Terhadap Efektivitas Iklan Aqua Versi Ada Aqua Di Kabupaten Brebes - Euis Tati Haryani; Monika Indrasari; Dwi Harini; Hendri Sucipto; Nur Khojin (CV. Aksara Global Akademia, 2023)
An increasingly intensive marketing strategy is carried out by advertising on television, including advertisements for Aqua brand Bottled Drinking Water (AMDK) products. Aqua's strategy has been effective in accordance with the findings of the market research conducted. The purpose of this study was to understand the impact of the effectiveness of Aqua advertising 'existing version of Aqua'. The quantitative approach method carried out is based on positivistic research data (concrete data), namely numerical values to be measured using statistics as a calculation test tool, related to the problem under study to produce a conclusion. The population of this study was the entire audience of Aqua television commercials in Brebes County. The sample was obtained with the 10% Slovin formula of 200 respondents. The research instrument used was in the form of primary data from filling out questionnaires. The results showed that advertising creativity and humor elements had a positive effect on the effectiveness of Aqua advertisements, there was a positive influence of advertising attractiveness on the effectiveness of Aqua advertisements, the quality of advertising messages had a positive effect on advertising effectiveness and there was an influence on advertising creativity, humor elements, advertising attractiveness and quality of advertising messages simultaneously affected the effectiveness of Aqua advertisements in Brebes Regency